Single-center experience of extracorporeal membrane oxygenation mainly anticoagulated with nafamostat mesilate - Han, Woosik (J Thorac Dis, 2019)
BACKGROUND: Bleeding remains the chief concern during extracorporeal membrane oxygenation (ECMO). Recently, several studies proposed nafamostat mesilate (NM) as an alternative anticoagulant to heparin due to reduced bleeding complications and comparable thromboembolic episodes. The aim of this study was to evaluate the clinical outcomes of ECMO anticoagulated mainly with NM. METHODS: This was a retrospective observational case series of patients who were placed on ECMO between January 2011 and December 2017 at Chungnam National University Hospital. The main outcomes were bleeding and thromboembolic episodes. RESULTS: During the study period, a total of 91 ECMO runs on 87 patients were identified. There were 54 veno-venous runs and 37 veno-arterial runs. Among the 87 patients, 47 (54.0%) patients were successfully weaned and 29 (33.3%) survived to discharge. Most of the runs were anticoagulated with NM (n=68, 74.7%), followed by heparin (n=22, 24.2%) and argatroban (n=1, 1.1%). The mean duration of ECMO support was 11.3±11.1 days. The overall incidence of bleeding was 46.2% (n=42); 26 runs were anticoagulated with NM (26/68, 38.2%) and 16 with heparin (16/22, 72.7%) (P=0.005). The overall incidence of thromboembolic episodes was 12.1% (n=11). In the NM group, the incidence of hyperkalemia requiring any type of intervention was 17.6% (n=12). CONCLUSIONS: In this single center study, NM appears to be associated with fewer bleeding complications during ECMO without increasing the incidence of thromboembolic episodes.